"There Is No Treatment Here:" Disability and Health Needs In A State Prison System - Phil Smith (Disability Studies Quarterly, 2005)
To understand the disability and health needs of prisoners, the Vermont Prisoner's Health Coalition sent out a survey to every adult prisoner within the Vermont correctional system in the fall of 2002. Open-ended questions centered on disability, health care, and treatment received by inmates within the Vermont correctional system. 190 surveys were returned, and narrative responses were analyzed using qualitative research methods. Most respondents reported having some kind of disability, including learning, developmental, or psychiatric disabilities. Treatment and accommodations were described as inadequate or non-existent, and long wait times for services were typical. The importance of listening to the voices of prisoners regarding accommodations and supports for their disabilities, and perceptions of the quality of their health care, is emphasized.
Keywords: prisoners with disabilities; Vermont Prisoner' s Health Coalition; psychiatric disabilities; learning disabilities; developmental disabilities; medical care for prisoners